NaIO4/KI/NaCl: a new reagent system for iodination of activated aromatics through in situ generation of iodine monochloride - Emmanuvel, Lourdusamy; Shukla, Ravi Kant; Sudalai, Arumugam; Gurunath, Suryavanshi; Sivaram, Swaminathan (Tetrahedron Letters, 2006)
A new reagent system consisting of NaIO4/KI/NaCl in aq AcOH has been found to be effective in iodinating a variety of activated aromatic substrates via in situ-generated iodine monochloride, to furnish iodoaromatics in excellent yields. This iodination procedure has been applied successfully for a cost-effective synthesis of 3,3'-diaminobenzidine, a key intermediate for preparing proton conducting membranes for fuel cell applications, with high yield and a purity of 99.7%. (c) 2006 Elsevier Ltd. All rights reserved.